2008
DOI: 10.2528/pierc08012301
|View full text |Cite
|
Sign up to set email alerts
|

Homomorphic Enhancement of Infrared Images Using the Additive Wavelet Transform

Abstract: Abstract-This paper presents a new enhancement technique for infrared images. This technique combines the benefits of homomorphic image processing and the additive wavelet transform. The idea behind this technique is based on decomposing the image into subbands in an additive fashion using the additive wavelet transform. This transform gives the image as an addition of subbands of the same resolution. The homomorphic processing is performed on each subband, separately. It is known that the homomorphic processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The homomorphic filtering techniques have shown that they are capable of compressing the dynamic range and enhancing the contrast simultaneously [2,3]. They concentrate on reinforcing the details of the image to be enhanced in terms of the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homomorphic filtering techniques have shown that they are capable of compressing the dynamic range and enhancing the contrast simultaneously [2,3]. They concentrate on reinforcing the details of the image to be enhanced in terms of the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional mapping gain used in the wavelet sub-bands for the noise suppression and the contrast enhancement is experimentally determined [2,3]. Since a feature of image object is very difficult to express mathematically, finding an optimal mapping gain for the feature extraction and a structuring element for the morphological filter is difficult and time-consuming task by trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional mapping gain used in the wavelet sub-bands for the noise suppression and the contrast enhancement is experimentally determined [1]- [3]. Since a feature of image object is very difficult to express mathematically, finding an optimal mapping gain for the feature extraction and a structuring element for the morphological filter is difficult and time-consuming task by trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelet and homomorphic filtering techniques have shown that they are capable of compressing the dynamic range and enhancing the contrast simultaneously [1]- [3]. They concentrate on reinforcing the details of the image to be enhanced in terms of the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation